2019
DOI: 10.1038/s41598-019-38530-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of post-hatching maturation on the pharmacokinetics of paracetamol in zebrafish larvae

Abstract: Zebrafish larvae are increasingly used in pharmacological and toxicological studies, but it is often overlooked that internal exposure to exogenous compounds, rather than the incubation medium concentration, is driving observed effects. Moreover, as the zebrafish larva is a developing organism, continuous physiological changes impact pharmacokinetic or toxicokinetic processes like the absorption and elimination of exogenous compounds, influencing the interpretation of observations and conclusions drawn from ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 33 publications
5
34
0
Order By: Relevance
“…Contrary to the bromine case, the 4-iodophenol showed a more dynamic behavior: With continuing exposure and ZFE development, the iodine is transferred from the yolk to the GI tract. This may be explained by an increased metabolizing capacity of older ZFEs [ 42 , 43 ] as well as the development of the elimination pathways via the liver and kidney [ 44 ]. It has recently been shown that the distribution of toxicants between the yolk and the ZFE body of developing ZFEs can be highly dynamic [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to the bromine case, the 4-iodophenol showed a more dynamic behavior: With continuing exposure and ZFE development, the iodine is transferred from the yolk to the GI tract. This may be explained by an increased metabolizing capacity of older ZFEs [ 42 , 43 ] as well as the development of the elimination pathways via the liver and kidney [ 44 ]. It has recently been shown that the distribution of toxicants between the yolk and the ZFE body of developing ZFEs can be highly dynamic [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Quantification of internal drug exposure in zebrafish larvae after external, waterborne drug treatment is essential for reliable interpretation of drug response, but because of small sample volumes and low concentrations, this is not straightforward. We have built upon recent work to develop an ultraā€sensitive LCā€“MS based quantification method (Kantae et al, 2016; Van Wijk, Krekels, Kantae, Harms, et al, 2019; Van Wijk, Krekels, Kantae, Ordas, et al, 2019). This methodology proved sensitive enough to quantify isoniazid in larval homogenates and blood samples of only nanolitres in volume.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of our paradigm compound paracetamol (acetaminophen), internal paracetamol amounts were subsequently used to quantify the pharmacokinetic processes of absorption and elimination through quantification of the rate of absorption and a clearance relative to total larval volume. Although the clearance derived from relative values in zebrafish larvae scaled quite reasonably to reported absolute clearance values in higher vertebrates ((Kantae et al, 2016;Van Wijk et al, 2019)), accurate scaling of clearance requires absolute clearance values in zebrafish larvae. However, quantification of absolute clearance requires blood concentrations, which will also allow for the estimation of a distribution volume, but blood-sampling methods for zebrafish larvae that are only a few hundred nanoliters in total volume (Guo et al, 2017) have not yet been described.…”
Section: Introductionmentioning
confidence: 91%